Natura ed evoluzione delle rocce ultramefiche in Calabria settentrionale - Caparelli, Sabina; Pantano, Pietro; Bloise, Andrea; Piluso, Eugenio (My University, 2018)
Continental Sila and oceanic Gimigliano-Monte Reventino tectonometamorphic Units that outcrop in northern Calabria contain small ultramafic rocks bodies. The ultramafic rocks of the Sila Unit are embedded within the northern Calabria alpine chain and preserve evidence of the pre-alpine extensional tectonics related to lithospheric thinning in Permo-Triassic time. The Sila Unit consist of a continuous continental lithospheric section in which the ultramafic rocks represent the subcontinental upper mantle components. The ultramafic rocks of the Gimigliano-Monte Reventino Unit represent the suboceanic upper mantle and was interpreted as remnants of the Jurassic Alpine Tethys ocean realms subsequently involved in the Alpine accretionary wedge. The mantle rocks of the Sila Unit are made of layered alternations of serpentinized peridotities and concordant pyroxenites. The serpentinites are after Spl-harzburgites-dunites. The concordant pyroxenites range from olivine-bearing orthopyroxenite to orthopyroxenite in composition. The olivine-bearing orthopyroxenites and the orthopyroxenites have been produced by melt-rocks interaction processes under Spl-lherzolitic facies conditions. Locally the concordant pyroxenites shows extensional tectonic effects whit formation of drawn boudins. The subsolidus evolution of the Sila Unit upper mantle rocks can be described by four main stages from Spl-lherzolite facies to Chl-lherzolite facies followed by a severe serpentinization. Moreover, evidence of metasomatism produced by melt-rock interaction has been observed at meso- and microscale. On the base of field work and microstructural evidence two main metasomatizing agents have been observed: (i) discordant dykes orthopyroxenitic in composition; (ii) concordant orneblendites with tholeitic affinity. Melt-rock interaction processes was responsible for the local transformation of: (i) Spl-peridotites into hercynitic spinel-bearing peridotites and (ii) concordant pyroxenites into websterites. Gabbroic magmatism occurred at P ≈ 0.55 GPa (Liberi et al., 2011). Thermobarometric estimates based on Opx-Cpx pairs from olivine-bearing othopyoxenites and websterites given values of 808-855°C and 0,7 GPa respectively for T and P. These physical conditions are consistent with the transition from Spl- to Amph-lherzolite facies. Finally, greenschist facies retrogression is documented by static serpentinization and by the development of late vein systems filled by serpentine mineral groups. At this stage chrysotile and lizardite crystallize. This fact suggests equilibrium at T<300°C. The serpentinites and ophicarbonates occur in the Gimigliano-Monte Reventino Unit at the core of the antiform structures. The serpentinites are after depleted lherzolites and in some preserve the protogranular textures. The ophicarbonate shows typical brecciated textures given by clasts of peridotites severely serpentinized surrounded by a matrix made of carbonates and serpentine minerals. The ultramafic rocks are in tectonic contact with the metabasites along a narrow cataclastic-mylonitic shear zone where can be observed a grain size reduction of serpentinite clasts in a matrix made of calcite and tremolite. Therefore, the petrogenetic evolution of the northern Calabria ultramafic rocks document a Ocean Continent Transition (OCT) which was part of the Tethyan hyperextended margin. Again, northern Calabrian ultramafics preserve the signals of the transition from late-hercinian orogenic extention to Tethyan rift, followed by the Alpine and subsequent compression stages in the Apennine tectonic phases.
Dottorato di Ricerca in Scienze e Ingegneria dell'Ambiente, delle Costruzioni e dell'Energia. Ciclo XXIX
Keywords: Rocce ignee